Analysis of Factors Affecting the Acceptance and Use of the Qlola BRI Platform Using the UTAUT Model (A Study on Non-Individual Customers at BRI Central Park Sub-Branch Office) - Perdana, Mas Bangkit Wira; Tricahyono, Dodie (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Digital transformation is revolutionizing global business, prompting all industries, including banking, to embrace digital technologies, with BRI leading the way through innovations like the BRI Cash Management System (CMS) to cater to evolving customer demands. This study examines the factors influencing the behavioral intention and use behavior of non-individual customers in adopting the Qlola BRI digital banking application. Using the UTAUT model, the research highlights that performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioral intention significantly impact the adoption and usage of Qlola BRI. Additionally, the moderating role of user experience was found to significantly strengthen the influence of effort expectancy on behavioral intention, while weakening the effect of social influence. However, experience did not significantly moderate the relationship between facilitating conditions and use behavior. The findings suggest that companies with higher experience rely more on their own judgment rather than social influence when deciding to use digital banking technologies. This study provides valuable insights for banks and financial institutions to enhance user adoption strategies by focusing on ease of use, performance benefits, and reliable support infrastructure.